In-depth Sentiment Analysis of The Independent Campus Program in Islamic Higher Education using Abstractive Summarization - Dian Sa'adillah Maylawati; Muhammad Indra Nurardy Saputra; Umar Syahrifudin; Aldi Fahluzi Muharam (Khazanah Pendidikan Islam, 2024)
The implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy in Islamic Higher Education (PTKI) represents a significant shift in Indonesia’s education system. This study evaluates the impact of MBKM on PTKI institutions using sentiment analysis and automatic text summarization. By analyzing 2,416 tweets (2020-2023) from PTKI academics, this study highlights perceptions, challenges, and policy implications. Results indicate that 82.76% of tweets expressed positive sentiment, emphasizing the benefits of MBKM in curriculum flexibility and industry collaboration. However, 17.24% of tweets highlighted challenges, including policy mismanagement, unclear implementation, and student stress. To enhance policy effectiveness, this study recommends stronger institutional support, clearer policy guidelines, and enhanced digital infrastructure to ensure MBKM benefits all PTKI students equitably.